E-commerce (B2C) evaluation practices: A pilot study on Jordanian consumers' perspectives - Ahmad, Faudziah; Yahaya, Jamaiah; Tarawneh, Omar; Baharom, Fauziah; Abd Wahab, Alawiyah (2011)
Many websites fail to help companies reach their objectives because they neglect consumers need in their websites developments.Since consumers are considered as the key success factor for sustaining B2C business, companies must therefore identify their consumers’ behavioral characteristics. The pilot study aims to investigate the quality factors of B2C web-sites from consumers’ perspectives. Specifically, t he study investigates the current practice towards quality development on Jordanian B2C websites in terms of degree of satisfaction, online buying habits of B2C consumers, ob- stacles and constraints surrounded B2C ecommerce websites, and factors that consumers consider when evaluating B2C websites.Data was collected through questionnaire and interviews.Descriptive statistics such as mean, frequency calculation, and percentages were used for analysis.Out of 33 quality factors, 17 have been found to be important.These are: web site visibility; safety; serviceability; price savings; high responsiveness; online shops credibility; enjoyment and entertainment; web sites information; the value of the web; promotion activities; clarity; relevance; diversity of goods, services and information; current and updated web documents;user-friendly web interface; trust or trustworthiness; and accuracy and authority of web documents.